2019
DOI: 10.1002/ps.5525
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of afidopyropen against soybean aphid (Hemiptera: Aphididae) and toxicity to natural enemies

Abstract: BACKGROUND Soybean aphid, Aphis glycines (Hemiptera: Aphididae), remains the most significant soybean insect pest in the North Central Region of the USA. The sustainability of reliance on only a few insecticide groups for this pest is questionable. We evaluate afidopyropen, a novel pyropene insecticide (Group 9D), for efficacy against A. glycines in field and greenhouse experiments and toxicity to common natural enemies in laboratory experiments. RESULTS Across 4 site‐years of field experiments and a greenhous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 53 publications
2
30
0
Order By: Relevance
“…A study conducted on green peach aphid and its predator, the two spotted ladybeetle (Adalia bipunctata L.) (Coleoptera: Coccinellidae), found a significant difference in green peach aphid numbers between pre-and post-treatment but found no significant difference in two spotted ladybeetle larvae under the same parameters [14]. A laboratory study with soybean aphid found low toxicity to convergent ladybeetle (Hippodamia convergens Guerin-Meneville) (Coleoptera:Coccinellidae) and moderate toxicity to Aphelinus certus Yasnosh (Hymenoptera: Aphelinidae) [32]. The results of our study are similar to these results.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted on green peach aphid and its predator, the two spotted ladybeetle (Adalia bipunctata L.) (Coleoptera: Coccinellidae), found a significant difference in green peach aphid numbers between pre-and post-treatment but found no significant difference in two spotted ladybeetle larvae under the same parameters [14]. A laboratory study with soybean aphid found low toxicity to convergent ladybeetle (Hippodamia convergens Guerin-Meneville) (Coleoptera:Coccinellidae) and moderate toxicity to Aphelinus certus Yasnosh (Hymenoptera: Aphelinidae) [32]. The results of our study are similar to these results.…”
Section: Discussionmentioning
confidence: 99%
“…It is relatively non‐toxic to natural enemies and might be considered an effective option for IPM and IRM programs for soybean aphid ( Aphis glycines ) 16 …”
Section: Novel Mechanisms Of Actionmentioning
confidence: 99%
“…It has been reported that afidopyropen can be used as an effective measure for controlling notorious sucking and piercing insect pests, such as Aphis glycines Matsumura (Hemiptera: Aphididae), Monelliopsis pecanis Bissell (Hemiptera: Aphididae), B. tabaci, Diaphorina citri Kuwayama (Hemiptera: Liviidae), and Stephanitis pyrioides Scott (Hemiptera: Tingidae) [13][14][15][16][17]. the relative lack of toxicity of afidopyropen to natural enemies means, that along with other selective chemical agents, afidopyropen can be beneficial to integrated biological and chemical pest management; for example, afidopyropen was not toxic to Hippodamia convergens Guerin-Meneville (Coleoptera: Coccinellidae) and Orius insidiosus Say (Hemiptera: Anthocoridae), which are important natural enemies of A. glycines [18,19]. Additionally, afidopyropen provides an alternative chemical control option from a novel insecticide group, beyond the three that are currently heavily relied upon and alternated, that could be employed to aid in insecticide resistance avoidance and management programs, and considering that afidopyropen displays a new mechanism of killing insect pests, the application of afidopyropen is one hopeful supplement to common insecticides.…”
Section: Introductionmentioning
confidence: 99%